The underground girls of Kabul : in search of a hidden resistance in Afghanistan - Nordberg, Jenny (Crown Publishers, 2014)
An award-winning foreign correspondent who contributed to a Pulitzer Prize-winning New York Times series reveals the secret Afghan custom of disguising girls as boys to improve their prospects, discussing its political and social significance as well as the experiences of its practitioners.